IDDF2020-ABS-0020 Monitoring adherence to gluten-free diet using mean platelet volume in children with celiac disease. (18th November 2020) - Kumar, Deepak; Gupta, Garima
Abstract : Background: Celiac disease was thought to be uncommon, but now cases are prevalent worldwide. It is an autoimmune disease with the genetic susceptibility of the patient to gluten-containing food. The only treatment available is a gluten free diet. Compliance to the gluten-free diet and its monitoring becomes important and is difficult to follow in the pediatric patients. There are various invasive and non-invasive investigations available to monitor compliance. However, their availability and cost always remain an issue at low-resource health set-ups. MPV (Mean Platelet Volume) is a non-invasive, economic and easily available marker that can be used safely. Methods: Mean Platelets volume was measured on newly diagnosed celiac disease children between 3 to 12 years at baseline and after 3 months of starting Gluten-free diet. Total no. of patients n=35, M:F ratio- 1.1. Recurrent diarrhea (85%), pain abdomen (50%) and distension (45%) were the common abdominal symptoms. Anemia, Short stature and malnutrition were present in more than 90% of patients. The screening was done with TTG, and cases were confirmed with Duodenal biopsy. Marsh 3A was present in 5%, 3B in 52% and 3C in 43%. Mean Baseline MPV was 9.55 fL. Results: Patients were started on a gluten-free diet, they were followed monthly for symptoms or any new event, at the end of 3 months of follow up MPV was done, we observed that MPV was decreased from mean baseline level of 9.55 fL to 8.42 fL. (P 0.001). Conclusions: Reversibility of tissue changes after introduction to gluten-free diet remains the gold standard to see the improvement. However, it is an invasive procedure and an impractical method to follow up, especially in children. Other markers are not easily available at all health centers, specifically at developing and underdeveloped parts of the world. MPV can be used as a biomarker to see diet adherence and improvement in patients suffering from Celiac Disease. It has a disadvantage that high values can be found if there is associated co-infection or Iron Deficiency Anemia, which should be corrected before making any interpretation.